Iconic Associations Between Vowel Acoustics and Musical Patterns, and the Musical Protolanguage Hypothesis - Fenk-Oczlon, Gertraud (Frontiers in Communication, 2022)
Vowels are the most musical and sonic elements of speech. Previous studies found non-arbitrary associations between vowel intrinsic pitch and musical pitch in senseless syllables. In songs containing strings of senseless syllables, vowels are connected to melodic direction in close correspondence to their intrinsic pitch or the frequency of the second formant F2. This paper shows that also vowel intrinsic duration is related to musical patterns. It is generally assumed that low vowels like [a ɔ o] have a higher intrinsic duration than high vowels like [i y u] and that there is a positive correlation between the first formant F1 and duration. Analyzing twenty traditional Alpine yodels I found that vowels with longer intrinsic duration tend to align with longer notes, whereas vowels with shorter intrinsic duration with shorter notes. This new result might shed some light on size-sound symbolism in general: Since there is a direct match between vowel intrinsic duration and the ‘size’ of musical notes, there is no need to explain the ‘size’ of musical notes via Ohala’s ‘frequency code’ hypothesis. Moreover, I will argue that the iconic associations found between vowel acoustics and musical patterns support the idea of a sound-symbolic musical protolanguage. Such a protolanguage may have started with vowel syllables conveying pitch, timbre, as well as emotional, indexical, and sound-symbolic information